MENGHUBUNGKAN MASA LALU DAN KONSEP MATEMATIKA DENGAN PENDEKATAN HISTORIS DALAM PENDIDIKAN - Frisnoiry, Suci; Situmorang, Glory Indah; Purba, Rahel Dominggo; Br Ginting, Clara Yolanda; Panjaitan, Jelika; Najwa, Almaulidah (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2024)
This study aims to explore the importance of connecting the past with mathematical concepts through a historical approach in education. In the context of mathematics education, a historical approach can help students understand the development of mathematical concepts and their relevance to everyday life. By presenting the history behind mathematical discoveries, students can see the connections between theory and practice, enhancing their interest and motivation to learn. This research uses a qualitative method with data analysis from various national sources, including previous studies and educational curricula. The findings are expected to provide new insights for educators in implementing a historical approach in mathematics learning, along with recommendations for developing a more contextual curriculum.